Collaborative Governance in the Control of Street Vendors on Jendral Urip Sumoharjo Street - Citra Nugraheny Putri Widodo; Ismi Dwi Astuti Nurhaeni; Rina Herlina Haryanti (Al-Makki Publisher, 2023)
Street vendors are often the cause of disturbances in public peace and order, including in Surakarta City, especially on Jendral Urip Sumoharjo Street. Jendral Urip Sumoharjo Street is an orderly area in Surakarta City and is often the center of major events. The purpose of this study is to map the process of collaboration between stakeholders in regulating street vendors on Jendral Urip Sumoharjo Street. Analysis is seen from three components, namely principled engagement, shared motivation and capacity for joint action. This research uses qualitative research methods with a case study approach. Data collection techniques with interviews, observation and documentation. The data analysis technique used is interactive analysis and the validity of the data used is a triangulation technique. The results showed that the process of collaboration between stakeholders in this regulation through three components. This can be seen from the principled engagement component that starts from what drives collaboration, namely the results of routine patrols and community complaints that enter Satuan Polisi Pamong Praja Surakarta City. Followed by a coordination meeting by several stakeholders to reach an agreement, but did not involve street vendors and the community. The component of shared motivation begins with mutual trust through the duties, functions and authorities of several stakeholders which are then manifested into a letter of assignment accompanied by their respective commitments. Ending with the component of capacity for joint actions through regulation based on established commitments.